P Pengembangan Buku Panduan Bimbingan Karier Berdasarkan Teori Trait and Factor - Nur Arifaizal Basri Faiz; Eko Darminto; Hadi Warsito Wiryosutomo (Indonesian Journal of Learning Education and Counseling, 2021)
This research is a research and development (R&D) using the Dick and Carey development model with subjects of material experts, media experts, linguists, guidance and counseling teachers, and class XI students at SMAN 2 Pamekasan, SMAN 3 Pamekasan, SMAN 5 Pamekasan with a total of 18 students. The data was collected by interviews, questionnaires, career guidance treatment using a career guidance guide book based on the trait and factor theory. The data obtained in qualitative and quantitative. The results of the study at (1) the level of need for a career guidance guidebook based on the trait and factor theory with the Guidance and Counseling teacher's responses were stated to be very useful to use, (2) the results of the validation assessment results of material experts, media experts, and linguists showed a very feasible category, (3) the results of individual assessments of BK teachers at SMAN 2 Pamekasan are declared fit for use, (4) the results of small group assessments at SMAN 3 Pamekasan and SMAN 5 Pamekasan show very feasible and useful as a guide for career guidance services, (5) career guidance manual based on the theory of effective trait and factors based on the average data increase in the pre-test and post-test questionnaire scores of class XI students.